2018
DOI: 10.3390/languages3030034
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Short-Term Phonetic Interference in Bilingual Speech

Abstract: Previous research indicates that alternating between a bilingual's languages during speech production can lead to short-term increases in cross-language phonetic interaction. However, discrepancies exist between the reported L1-L2 effects in terms of direction and magnitude, and sometimes the effects are not found at all. The present study focused on L1 interference in L2, examining Voice Onset Time (VOT) of English voiceless stops produced by L1-dominant Czech-English bilinguals-interpreter trainees highly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Vowel chart for oral monophthongs in Bengali, from Ghosh (2016) performance interference (Paradis, 1993)). Given their transient nature, dynamic changes in production during mixed-language use are generally attributed to the latter, e.g., online processing costs (Olson, 2013;Šimáčková & Podlipskỳ, 2015;Tsui, Tong, & Chan, 2019, VOT), language mode (Simonet, 2014, vowel quality), context-awareness (Khattab, 2013, phonological variables). What triggers this interaction?…”
Section: What Causes Transfer and What Does It Affect?mentioning
confidence: 99%
See 1 more Smart Citation
“…Vowel chart for oral monophthongs in Bengali, from Ghosh (2016) performance interference (Paradis, 1993)). Given their transient nature, dynamic changes in production during mixed-language use are generally attributed to the latter, e.g., online processing costs (Olson, 2013;Šimáčková & Podlipskỳ, 2015;Tsui, Tong, & Chan, 2019, VOT), language mode (Simonet, 2014, vowel quality), context-awareness (Khattab, 2013, phonological variables). What triggers this interaction?…”
Section: What Causes Transfer and What Does It Affect?mentioning
confidence: 99%
“…(i) in the absence of other manipulations, productions in a bilingual language mode show increased cross-language influence compared to a monolingual mode (Simonet, 2014;Simonet & Amengual, 2020, vowel quality); (ii) (however, language mode is not the sole source of influence during mixed language usestudies comparing switched and nonswitched tokens produced in the same test block (identical language mode) (Olson, 2016;Tsui et al, 2019, VOT), or spontaneous conversation (Piccinini & Arvaniti, 2015, VOT), have still reported a difference, suggesting that independently of mode, switching between languages triggers a local increase in cross-language transfer; (iii) how the two sources interact to influence the final outcome of transfer is not fully understood: Olson (2016, VOT) found no additive effects of language mode, Olson (2013, VOT) found a balanced language context to inhibit transfer compared to unbalanced contexts. Other studies have not analyzed the two separately, eliciting switched tokens in a bilingual test block and nonswitched tokens in a monolingual test block, separated by a few hours to days (Elias et al, 2017, vowel quality), (Antoniou, Best, Tyler, & Kroos, 2011;Bullock & Toribio, 2009;Schwartz, Balas, & Rojczyk, 2015;Šimáčková & Podlipskỳ, 2015, 2018.…”
Section: What Causes Transfer and What Does It Affect?mentioning
confidence: 99%
“…Do L1-Czech L2-English bilinguals, who are advanced non-immersion learners of English as a foreign language (EFL), produce /k/ with distinct VOT values in L2 English and L1 Czech? We expected them to do so based on observation of other learners from the same population (Šimáčková and Podlipský 2018). Nevertheless, demonstrating that the bilinguals could categorically separate their k-sounds in terms of VOT was necessary before investigating gradient VOT shifts induced by switching.…”
Section: Research Questionsmentioning
confidence: 99%
“…A paper by Šimáčková and Podlipský (2018) investigates the extent of first language (L1) phonetic interference in the bilingual vs. monolingual mode for late adult Czech-English bilinguals who were training as interpreters. A previous study by the same authors had found that code-switching led to more Czech-influenced speech in L2 English than in monolingual English productions, but in the previous study not all participants had training in interpreting.…”
mentioning
confidence: 99%